2014
DOI: 10.1039/c3em00555k
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance, plasmid-mediated quinolone resistance (PMQR) genes and ampC gene in two typical municipal wastewater treatment plants

Abstract: Antibiotic resistant bacteria and plasmid-mediated quinolone resistance genes and ampC gene were investigated for Escherichia coli isolates from two typical municipal wastewater treatment plants in both dry and wet seasons by using the antibiotic susceptibility test and PCR assay, respectively. The results showed that 98.4% of the isolates (1056) were found resistant to antibiotic(s) tested and 90.6% showed multiple resistances to at least three antibiotics. Tetracycline was found to have the highest resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Many studies have investigated and confirmed the prevalence of various kinds of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the WWTPs of various countries (Reinthaler et al, 2003;Zhang and Zhang, 2011;Bouki et al, 2013;Su et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated and confirmed the prevalence of various kinds of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the WWTPs of various countries (Reinthaler et al, 2003;Zhang and Zhang, 2011;Bouki et al, 2013;Su et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All qPCR assays were performed on ViiA™ 7 Real-Time PCR System (ABI, USA) using SYBR Green Real Time QPCR Kit (TOYOBO, Japan). The detailed DNA extraction, purification and ARG determination methods can be referred to our previous study (He et al, 2014;Su et al, 2014aSu et al, , 2014b). …”
Section: Dna Extraction and Arg Quantificationmentioning
confidence: 99%
“…The transfer of antibiotic resistance determinants from human and livestock sources to the environment has gained attention in the scientific community in the past decade (Silbergeld et al, 2008;Storteboom et al, 2010;Wright, 2010), with antibiotic resistance genes (ARGs) considered as emerging environmental contaminants (Pruden et al, 2006). Human wastes are nowadays better treated by centralized wastewater treatment plants than animal wastes with simple treatment systems such as lagoon and digester or even without any treatment before their discharge into the environment (McKinney et al, 2010;Liu et al, 2012;Zhou et al, 2013;He et al, 2014;Su et al, 2014b;Chen et al, 2015). In comparison with other livestock animals (broiler and cattle), antibiotics are commonly used as growth promoter in swine farming (Zhou et al, 2013;Durso and Cook, 2014), thus swine feedlots are of particular concern as potential hot spots for promoting the dissemination of antibiotic resistance (Gotz and Smalla, 1997;Cole et al, 2000;Binh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…China as one of the world's largest aquatic producing countries, is also the largest producer and consumer of antibiotics in the world. The average annual yield of antibiotics in China is about 210000t, including about 46% of antibiotics accounted in livestock and aquaculture [6]. The results showed that three kinds of antibiotics were detected in the coastal aquaculture area of Jiulong River, Fujian Province, China.…”
Section: Status Of Antibiotic Pollution In Coastal Wetlandsmentioning
confidence: 75%